Pembuatan Mesin Pencetak Adonan Kue Kacang Intip Modifikasi Model Roll Cutting Dengan Variasi Bentuk Hasil Cetakan Kapasitas 10 kg/jam - Nurdiana; Sagala, Mahendra Saut Parlindungan (CV. IRA PUBLISHING, 2022)
From the results of the modified design of the Peanut Peanut Cake Molding machine on the roll cutting system with variations in the shape of the printout with a capacity of 10 kg/hour, the main components of this machine are 1 drive shaft, 2 pressing rolls, 2 roll conveyors, 1 blade, engine frame, 1 set of conveyor belts as well as engine supporting components such as bearings, driving motors, chains, sprockets, reducers. The next step is to determine the working steps of component manufacture and determine the tools and tools used for component manufacture, including steel rulers, cutting grinders, welding machines, hand grinders, and lathes. From the results of the calculation time for the component manufacturing process to assembly, making the engine mount frame is 4.2 hours, making the drive shaft 3.37 hours, making a roll press 2.2 hours, making a roll conveyor 2.1 hours, making a shaft connection 2.4 hours. , making blades 15.17 hours, making the inlet 1.68 hours, making the outlet 1.53 hours, and machine assembly 5.88 hours. Based on the analysis of making a total processing time of 38.69 hours, the actual time to work until the assembly of the Peanut Peanut Cookie dough molding machine was modified by roll cutting with variations in the shape of the mold for 38.69 hours, the work efficiency of this machine is estimated to be 80% and the processing time is 48.36 hours.